Genetic variants associated with drugs‐induced immediate hypersensitivity reactions: a PRISMA‐compliant systematic review. Issue 4 (29th January 2016) - Oussalah, A.; Mayorga, C.; Blanca, M.; Barbaud, A.; Nakonechna, A.; Cernadas, J.; Gotua, M.; Brockow, K.; Caubet, J.‐C.; Bircher, A.; Atanaskovic, M.; Demoly, P.; et al.
Abstract: Drug hypersensitivity includes allergic (AR) and nonallergic reactions (NARs) influenced by genetic predisposition. We performed a systematic review of genetic predictors of IgE‐mediated AR and NAR with MEDLINE and PubMed search engine between January 1966 and December 2014. Among 3110 citations, the search selected 53 studies, 42 of which remained eligible. These eligible studies have evaluated genetic determinants of immediate reactions (IR) to beta‐lactams ( n  = 19), NAR against aspirin ( n  = 12) and other nonsteroidal anti‐inflammatory drugs (NSAIDs) ( n  = 8), and IR to biologics ( n  = 3). We reported two genomewide association studies and four case–control studies on candidate genes validated by replication. Genes involved in IR to beta‐lactams belonged to HLA type 2 antigen processing, IgE production, atopy, and inflammation, including 4 genes validated by replications, HLA‐DRA, ILR4, NOD2, and LGALS3 . Genes involved in NAR to aspirin belonged to arachidonic acid pathway, membrane‐spanning 4A gene family, histamine production pathway, and pro‐inflammatory cytokines, while those involved in NAR to all NSAIDs belonged to arachidonic acid pathway and HLA antigen processing pathway. ALOX5 was a common predictor of studies on NAR to both aspirin and NSAIDs. Although these first conclusions could be drawn, this review highlights also the lack of reliable data and the need for replicating studies in contrasted populations, taking into account worldwide allele frequencies, gene–gene interactions, and contrasted situations of environmental exposure.